Middle managers and their strategic work - Rouleau, Linda (Henry Stewart Talks, 2014)
Middle managers research and SAP, Historical overview, Definition, Strategy work, Sensemaking practices, Discursive practices, Political practices, Institutional practices, Organizational ethnography, Self-report and biographical methods, Shadowing, Challenges, Future avenues of research